Hadith #4175 - Sahih al-Bukhari - Imran bin 'Uyaynah عمران بن عيينة (Sahih al-Bukhari)
A delegation from Banu Tamim came to the Prophet (ﷺ) . The Prophet (ﷺ) said, “Accept the good tidings, O Banu Tamim!” They said, “O Allah’s Messenger (ﷺ)! You have given us good tidings, so give us (something).” Signs of displeasure appeared on his face. Then another delegation from Yemen came and he said (to them), “Accept the good tidings, for Banu Tamim refuses to accept them.” They replied, “We have accepted them, O Allah’s Messenger (ﷺ)!”
Grade: Sahih

Hadith #7135 - Sahih al-Bukhari - Imran bin 'Uyaynah عمران بن عيينة (Sahih al-Bukhari)
While I was with the Prophet (ﷺ) , some people from Bani Tamim came to him. The Prophet (ﷺ) said, “O Bani Tamim! Accept the good news!” They said, “You have given us the good news; now give us (something).” (After a while) some Yemenites entered, and he said to them, “O the people of Yemen! Accept the good news, as Bani Tamim have refused it. ” They said, “We accept it, for we have come to you to learn the Religion. So we ask you what the beginning of this universe was.” The
Grade: Sahih